Strategi Pemasaran untuk Meningkatkan Volume Penjualan Tempe dengan 4P di UD. Alby Jaya - Syauri, Yayan Sifyan (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Marketing strategy is one of the important keys in the development of small and medium enterprises (SMEs), including trading businesses (UD) engaged in tempeh production. This research or report aims to analyze the implementation of marketing strategies with a 4P marketing mix approach (Product, Price, Place, Promotion) at UD. ALBY JAYA. The results of the analysis show that in terms of product, UD. ALBY JAYA focuses on cleanliness and quality, but is still limited in innovation in product variants. In terms of price, UD. ALBY JAYA sets competitive prices that are adjusted to consumer purchasing power. In terms of place (distribution), tempeh products are distributed to traditional markets, stalls, and through direct orders. For promotion, UD. ALBY JAYA still relies on word of mouth promotion and has not maximized the use of digital media